Correction: Enantioselective total synthesis of (−)-colchicine, (+)-demecolcinone and metacolchicine: determination of the absolute configurations of the latter two alkaloids. Issue 3 (13th December 2018) - Chen, Bo; Liu, Xin; Hu, Ya-Jian; Zhang, Dong-Mei; Deng, Lijuan; Lu, Jieyu; Min, Long; Ye, Wen-Cai; Li, Chuang-Chuang
Abstract : Correction for 'Enantioselective total synthesis of (−)-colchicine, (+)-demecolcinone and metacolchicine: determination of the absolute configurations of the latter two alkaloids' by Chuang-Chuang Li et al., Chem. Sci., 2017, 8, 4961–4966.